Efforts to Improve Numeracy Literacy Skills of Grade V Students of Elementary School 067694 Medan Through Differentiated Learning - Suwanto, Suwanto; Waluyo, Sujoko; Indriyani, Siti (International Journal Of Education, Social Studies, And Management (IJESSM), 2024)
Improving the Numeracy Literacy Skills of Grade V students at SD 067694 Medan is the main objective of this Classroom Action Research. Some high-class students still have difficulty in using mathematical symbols, difficulty interpreting existing data, and making decisions from the analysis they have done. Several efforts have been made such as reading books 15 minutes before entering class, but the results have not been significant in students' numeracy literacy skills. So it is necessary to focus more on smaller subjects in this case the class, and class V was chosen because it does not interfere with the program and for preparation for graduation later. The instruments used in this PTK consist of numeracy literacy test instruments, student activity observation sheets and interviews. The first action taken is to apply differentiated learning based on students' learning styles (Audio, Visual, and kinesthetic), obstacles found in cycle I related to the devices used and students' inflexibility in participating in group learning. In Cycle II, adjusting the condition of the device, and adjusting the number of learning media used. Of the four indicators of numeracy literacy that have increased, the indicator that appears to have a significant increase is the indicator of drawing conclusions. After the actions of cycle I and cycle II were carried out, the students' conclusions were more argumentative and provided quite appropriate reasons. Then, when viewed from the students' learning styles, the activities carried out by students in cycle II were more focused than in cycle I. However, from both cycles, students with a kinesthetic learning style in each learning activity were increasingly active, when participating in learning with learning media.